Microcirculatory tissue perfusion during general anaesthesia and noncardiac surgery: An observational study using incident dark field imaging with automated video analysis. Issue 7 (16th July 2022) - Flick, Moritz; Schreiber, Tim-Henrik; Montomoli, Jonathan; Krause, Linda; de Boer, Hans D.; Kouz, Karim; Scheeren, Thomas W.L.; Ince, Can; Hilty, Matthias P.; Saugel, Bernd
Abstract : BACKGROUND: Handheld vital microscopy allows direct observation of red blood cells within the sublingual microcirculation. Automated analysis allows quantifying microcirculatory tissue perfusion variables – including tissue red blood cell perfusion (tRBCp), a functional variable integrating microcirculatory convection and diffusion capacities. OBJECTIVE: We aimed to describe baseline microcirculatory tissue perfusion in patients presenting for elective noncardiac surgery and test that microcirculatory tissue perfusion is preserved during elective general anaesthesia for noncardiac surgery. DESIGN: Prospective observational study. SETTING: University Medical Center Hamburg-Eppendorf, Hamburg, Germany. PATIENTS: 120 elective noncardiac surgery patients (major abdominal, orthopaedic or trauma and minor urologic surgery) and 40 young healthy volunteers. MAIN OUTCOME MEASURES: We measured sublingual microcirculation using incident dark field imaging with automated analysis at baseline before induction of general anaesthesia, under general anaesthesia before surgical incision and every 30 min during surgery. We used incident the dark field imaging technology with a validated automated analysis software. RESULTS: A total of 3687 microcirculation video sequences were analysed. Microcirculatory tissue perfusion variables varied substantially between individuals – but ranges were similar between patients and volunteers. Under general anaesthesia before surgical incision, there were no important changes in tRBCp, functional capillary density and capillary haematocrit compared with preinduction baseline. However, total vessel density was higher and red blood cell velocity and the proportion of perfused vessels were lower under general anaesthesia. There were no important changes in any microcirculatory tissue perfusion variables during surgery. CONCLUSION: In patients presenting for elective noncardiac surgery, baseline microcirculatory tissue perfusion variables vary substantially between individuals – but ranges are similar to those in young healthy volunteers. Microcirculatory tissue perfusion is preserved during general anaesthesia and noncardiac surgery – when macrocirculatory haemodynamics are maintained.